The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.3389/fphys.2017.00795
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Tendon Thickness Adaptation in Adolescent Elite Athletes: A Longitudinal Study

Abstract: Increased Achilles (AT) and Patellar tendon (PT) thickness in adolescent athletes compared to non-athletes could be shown. However, it is unclear, if changes are of pathological or physiological origin due to training. The aim of this study was to determine physiological AT and PT thickness adaptation in adolescent elite athletes compared to non-athletes, considering sex and sport. In a longitudinal study design with two measurement days (M1/M2) within an interval of 3.2 ± 0.8 years, 131 healthy adolescent eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
(74 reference statements)
2
16
0
2
Order By: Relevance
“…The increase in tendon thickness and length with sport participation, at an earlier time from PHV may be an adaptive response to specific training-induced increase in muscle mass and strength ( Falk and Eliakim, 2003 , Waugh et al, 2014 , Granacher et al, 2011 ). Our findings are consistent with Cassel et al (2017) who reported greater tendon cross sectional area in athletes than non-athletes in specific sport activities. Nevertheless, our findings are in odds with other studies, which show that sports participation had no significant relationship with cross sectional area ( Waugh et al, 2014 , Neugebauer and Hawkins, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The increase in tendon thickness and length with sport participation, at an earlier time from PHV may be an adaptive response to specific training-induced increase in muscle mass and strength ( Falk and Eliakim, 2003 , Waugh et al, 2014 , Granacher et al, 2011 ). Our findings are consistent with Cassel et al (2017) who reported greater tendon cross sectional area in athletes than non-athletes in specific sport activities. Nevertheless, our findings are in odds with other studies, which show that sports participation had no significant relationship with cross sectional area ( Waugh et al, 2014 , Neugebauer and Hawkins, 2012 ).…”
Section: Discussionsupporting
confidence: 93%
“…One study, found that the patellar tendon CSA increased 27% from mid to late adolescence (16-18 years) ( Mersmann et al, 2017a ), whereas others report reductions in tendon cross sectional areas in early adolescence ( Neugebauer and Hawkins, 2012 ). These controversial reports about the tendon’s hypertrophy in childhood to adulthood could be attributed to the age cohort and the inclusion of adolescents who participated in sports or not ( Mersmann et al, 2017b , Cassel et al, 2017 ), and gender ( Intziegianni et al, 2017 ). Our findings from this longitudinal study show that athletes had greater cross-sectional area and longer resting length of the Achilles tendon than non-athletes.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that no differences between civilians and cadets were found for the AT agrees with a series of past findings pertaining to tendon‐specific structural and functional adaptations resulting from short‐term resistance training and long‐term habitual overloading. Combined evidence from a number of studies in athletic populations with controls suggest that the mechanical loading threshold for adaptations in the AT is somewhat higher than that of the PT in the same populations 4,10,11,13,14,29,45,50 . We can therefore deduce that the load exerted on the AT in the group of cadets was not sufficient to produce any changes in tendon thickness and CSA.…”
Section: Discussionmentioning
confidence: 82%
“…In this new oblique-sagittal view, the slice running through the midportion of the patellar tendon was identified, from which the longitudinal axis of the tendon was defined. The AP patellar tendon diameter was measured perpendicular to this longitudinal axis at a distance of 2 cm distal to the patella 7,8 on the slice displaying the thickest part of the tendon at that height (Figure 2).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%